Dinamika Kehidupan Nelayan Pangandaran 1970-2012: Transformasi Sosial Ekonomi dalam Konteks Negara Maritim - Fahmi, Rezza Fauzi Muhammad; Nurholis, Egi; Rahayu, Tiara Kirani; Meilani, Rosa; Apriliani, Alma; Ramadhan, Afiyah Armina (Jurnal Artefak, 2025)
The purpose of this research is to analyze the dynamics of Pangandaran fishermen's lives 1970-2012: socio-economic transformation in the context of a maritime nation. With a focus on social, economic and political changes in Indonesia as a maritime nation. During this period, fishermen shifted from traditional fishing gear to modern technology, increasing their catch and changing their economic mindset. This study highlights how technological changes, government policies, and globalization affect fishermen's lives and their impact on their welfare and community identity. The method used is the historical method through literature studies. Data are taken from primary and secondary sources, such as history books and journal articles. The results of this study indicate that in the midst of modernization, Pangandaran fishermen still maintain local traditions and maritime culture, reflecting their existence against changing times. The adaptation of fishermen in maintaining local traditions in the midst of modernization shows that maritime culture is not only a heritage, but also a potential to be developed as an identity and economic strength of a maritime nation. Comparative research is needed with other coastal areas in Indonesia to understand the pattern of fishermen's transformation in different cultural, geographical and policy contexts, as a basis for formulating a holistic national maritime strategy.